An Analysis of Thai Food Content on Social Media and the Construction of Soft Power - ครุยทอง, พรฤทัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine the characteristics of Thai food content on social media, to analyze the presentation formats of Thai cuisine, and to investigate the role of such content in promoting Thailand’s soft power. This research employed a descriptive research design using content analysis. A total of 100 Thai food-related contents were collected from social media platforms, including TikTok, YouTube, Facebook, and Instagram. The research instrument was a content analysis form developed by the researcher and validated for content validity by experts. The data were analyzed using percentage statistics.           The findings revealed that the most prevalent type of Thai food content was food reviews, accounting for 40%, followed by cooking demonstration content (25%) and street food content (20%). In addition, it was found that short-form video presentations and food review content played a significant role in disseminating Thai culinary culture and enhancing Thailand’s image at the international level. Overall, the results indicated that Thai food content on social media served as an important tool for strengthening soft power by increasing awareness of Thai culinary culture and promoting a positive image of Thailand among global audiences.